2020
DOI: 10.1021/acsami.9b22903
|View full text |Cite
|
Sign up to set email alerts
|

Poly(methyl methacrylate) Films with High Concentrations of Silicon Quantum Dots for Visibly Transparent Luminescent Solar Concentrators

Abstract: Silicon quantum dots (Si QDs) are attractive, nontoxic luminophores for luminescent solar concentrators (LSCs). Here, we produced Si QD/poly(methyl methacrylate) (PMMA) films on glass by doctor-blading polymer solutions and achieved films with low light scattering at an order of magnitude higher Si QD weight fraction than has been achieved previously in the bulk. We suggest that the fast solidification rate of films as compared to slow bulk polymerization is an enabling factor in avoiding large agglomerates wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…Quick solidification of PMMA leads to low light-scattering films with an order of magnitude higher QD weight fraction than previously reported nonscattering bulk-polymerized Si QD/PMMA nanocomposites. [164] 3D macroporous photonic crystals have been proposed for the fabrication of efficient photon reflectors for QD-coated LSCs. Characterization of a 2.8 × 1.5 × 0.1 cm device with an integrating sphere showed that adapting the reflection band to the emission profile of the QD emitter improves the light-trapping efficiency from 73.3% to 95.1%.…”
Section: Emitters Based On Qds and Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quick solidification of PMMA leads to low light-scattering films with an order of magnitude higher QD weight fraction than previously reported nonscattering bulk-polymerized Si QD/PMMA nanocomposites. [164] 3D macroporous photonic crystals have been proposed for the fabrication of efficient photon reflectors for QD-coated LSCs. Characterization of a 2.8 × 1.5 × 0.1 cm device with an integrating sphere showed that adapting the reflection band to the emission profile of the QD emitter improves the light-trapping efficiency from 73.3% to 95.1%.…”
Section: Emitters Based On Qds and Nanocrystalsmentioning
confidence: 99%
“…[167] The toxicity of classical QDs containing metals such as Cd or Pb has triggered the search for alternative nanomaterials as emitters. Besides the already discussed silicon QDs, [158,160,163,164] several groups have investigated CDs as possible nontoxic emitters. [161,[168][169][170][171][172][173][174][175][176] Zhou et al prepared CDs modified by a treatment with oleylamine in order to reduce absorption in long wavelengths, and thus, SA.…”
Section: Emitters Based On Qds and Nanocrystalsmentioning
confidence: 99%
“…Hill et al. investigated the performance of an LSC based on bare silicon QDs [166] . Si QDs of varying concentrations were embedded in PMMA and doctor bladed with various thicknesses onto glass to form LSC prototypes.…”
Section: Semiconductor Quantum Dots In Lscsmentioning
confidence: 99%
“…Although large scattering effects were noticeable even with a QD loading of 0.15 wt%, increasing the solidification rate decreased QD agglomerations and improved waveguide efficiency. A 1 % solidified LSC exhibited a high UV absorption>80 % and visible transmission>87 % with haze<1 % [166] . High light scattering of incident light off the nanoparticle's surface is an important factor for high absorption efficiency.…”
Section: Semiconductor Quantum Dots In Lscsmentioning
confidence: 99%
“…[ 3,11,14,15 ] Device efficiencies tend to be modest, with values of 7.1% [ 16 ] for a device employing GaAs photovoltaics (PVs) and 4.2% using silicon PV [ 17 ] being among the highest reported. Some other notable examples of conventional LSC design deployments include noise barriers, [ 13,18 ] artworks, [ 19,20 ] greenhouses, [ 21 ] roofing elements, [ 22 ] urban furniture, [ 23 ] and bicycle sheds, [ 23,24 ] and, in the more transparent state, building windows, [ 25,26 ] among others.…”
Section: Introductionmentioning
confidence: 99%